Performance Analysis of Femtocell Deployment in an Indoor LTE Cellular Networks - Laily Yusof, Azita; Arif Syafiq Mohamad Rohim, Mohamad; Ya’acob, Norsuzila; Mohd, Aziean (International Journal of Engineering and Technology, 2019)
Wireless communication has become an essential as the technology advanced and this creates a situation where a high capacity cell is needed to accommodate the needs of the public, especially in urban area. The cell that contained heavily loaded users became crowded and hence affected the signal performance. This situation will result in low signal strength received by the users, bad performance of the system and even drop call happened. This paper presents the performance analysis of femtocell deployment in indoor LTE cellular networks. In this study, to support this crowded cell, this research proposes deployment of femtocell which can enhance indoor coverage in Long Term Evolution (LTE) cellular networks. A femtocell is a small, low-power cellular base station, typically designed for use in a home or small business. Several test measurements at 3 different floor levels of shopping mall have been carried out by using Nemo Handy tool to see on signal strength variations. Based on the measurement analysis, a framework with femtocell deployment has been developed by using MATLAB software to improve the signal strength performance. The results demonstrated that femtocell deployment has improved handover successful rate and hence, provides better indoor coverage and network capacity for LTE cellular networks.Â Â